Screening of newborn infants for cholestatic hepatobiliary disease with tandem mass spectrometry. Issue 7208 (21st August 1999) - Mushtaq, Imran; Logan, Stuart; Morris, Michael; Johnson, Andrew W; Wade, Angie M; Kelly, Deirdre; Clayton, Peter T
Abstract: Objective: To assess the feasibility of screening for cholestatic hepatobiliary disease and extrahepatic biliary atresia by using tandem mass spectrometry to measure conjugated bile acids in dried blood spots obtained from newborn infants at 7-10 days of age for the Guthrie test. Setting: Three tertiary referral clinics and regional neonatal screening laboratories. Design: Unused blood spots from the Guthrie test were retrieved for infants presenting with cholestatic hepatobiliary disease and from the two cards stored on either side of each card from an index child. Concentrations of conjugated bile acids measured by tandem mass spectrometry in the two groups were compared. Main outcome measures: Concentrations of glycodihydroxycholanoates, glycotrihydroxycholanoates, taurodihydroxycholanoates, and taurotrihydroxycholanoates. Receiver operator curves were plotted to determine which parameter (or combination of parameters) would best predict the cases of cholestatic hepatobiliary disease and extrahepatic biliary atresia. The sensitivity and specificity at a selection of cut off values for each bile acid species and for total bile acid concentrations for the detection of the two conditions were calculated. Results: 218 children with cholestatic hepatobiliary disease were eligible for inclusion in the study. Two children without a final diagnosis and five who presented at <14 days of age were excluded. Usable blood spots were obtained from 177 index children and 708 comparison children. Mean concentrations of all four bile acid species were significantly raised in children with cholestatic hepatobiliary disease and extrahepatic biliary atresia compared with the unaffected children (P<0.0001). Of 177 children with cholestatic hepatobiliary disease, 104 (59%) had a total bile acid concentration >33 μmol/l (97.5th centile value for comparison group). Of the 61 with extrahepatic biliary atresia, 47 (77%) had total bile acid concentrations >33 μmol/l Taurotrihydroxycholanoate and total bile acid concentrations were the best predictors of both conditions. For all cholestatic hepatobiliary disease, a cut off level of total bile acid concentration of 30 μmol/l gave a sensitivity of 62% and a specificity of 96%, while the corresponding values for extrahepatic biliary atresia were 79% and 96%. Conclusion: Most children who present with extrahepatic biliary atresia and other forms of cholestatic hepatobiliary disease have significantly raised concentrations of conjugated bile acids as measured by tandem mass spectrometry at the time when samples are taken for the Guthrie test. Unfortunately the separation between the concentrations in these infants and those in the general population is not sufficient to make mass screening for cholestatic hepatobiliary disease a feasible option with this method alone.